Targeting oxidative stress in diabetic retinopathy: mechanisms, pathology, and novel treatment approaches - He, Wei; Tang, Panli; Lv, Hongbin (Frontiers in Immunology, 2025)
Diabetic retinopathy (DR) is a common and severe microvascular complication of diabetes, leading to vision impairment and blindness, particularly in working-age adults. Oxidative stress plays a central role in the pathogenesis of DR, with excessive reactive oxygen species (ROS) damaging retinal tissues, including blood vessels and neurons. This oxidative damage is exacerbated through various metabolic pathways, such as the polyol pathway, protein kinase C(PKC) activation, and advanced glycation end-product(AGE) formation. Additionally, mitochondrial dysfunction, retinal cell apoptosis, inflammation, and lipid peroxidation are key pathological processes associated with oxidative stress in DR. Epigenetic modifications, including DNA methylation and histone alterations, further contribute to gene expression changes induced by oxidative stress. To mitigate oxidative damage, therapeutic strategies targeting ROS production, neutralizing free radicals, and enhancing antioxidant defenses hold promise. Various natural antioxidant compounds, such as polyphenols (e.g., epigallocatechin-3-gallate, quercetin, resveratrol) and carotenoids (e.g., lutein, zeaxanthin), have demonstrated potential in reducing oxidative stress and improving retinal health in DR models. Moreover, activation of the Nrf2 and SIRT1 pathways has emerged as a promising approach to enhance the antioxidant response. Although preclinical studies show promising results, further clinical trials are necessary to validate the efficacy and safety of these therapeutic strategies. In conclusion, a better understanding of the molecular mechanisms underlying oxidative stress in DR and the development of multi-target therapies could provide more effective treatment options for DR patients.